2011
DOI: 10.1111/j.1751-7893.2011.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of suicide risk factors in people at ultra-high risk of developing psychosis: a service audit

Abstract: Suicide risk was high in this small sample of people at UHR of developing psychosis. Controlled research with larger samples and better methodology is urgently required to inform legal, ethical and scientific debates surrounding this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 18 publications
(23 reference statements)
7
31
1
Order By: Relevance
“…One previous study focusing on help-seeking young people who met ultra-high risk (UHR) criteria for psychosis demonstrated that nearly 20% of that group had engaged in serious self-harm during the time they were in contact with a specialized service (Hutton et al, 2011). As the majority of help-seeking individuals who are at high risk of developing psychosis have psychotic-like symptoms (Fusar-Poli et al, 2014), they might be a similar population to Group 5 in our study.…”
Section: Groupmentioning
confidence: 84%
“…One previous study focusing on help-seeking young people who met ultra-high risk (UHR) criteria for psychosis demonstrated that nearly 20% of that group had engaged in serious self-harm during the time they were in contact with a specialized service (Hutton et al, 2011). As the majority of help-seeking individuals who are at high risk of developing psychosis have psychotic-like symptoms (Fusar-Poli et al, 2014), they might be a similar population to Group 5 in our study.…”
Section: Groupmentioning
confidence: 84%
“…Research so far suggests that even in this population suicidal thinking and behavior may be prevalent (Taylor et al, 2014). In two samples of individuals at risk of psychosis a high prevalence of at least mild suicidal ideation over the preceding two weeks was observed (72.0-76.9%) (Hutton et al, 2011;Hui et al, 2013). Likewise, Welsh and Tiffin (2013) report that 30% of such individuals attempted suicide in the past six months in their sample.…”
Section: Introductionmentioning
confidence: 90%
“…Of those included in the study, 59% reported suicidal ideation and 21% engaged in acts of DSH. Previous work reported even greater risk, with 90% of a UHR sample reporting suicidal ideation during a 6 month period, and 25% attempting suicide at least once (Adlard, 1997, as cited in Hutton et al, 2011).…”
Section: Prevalence Of Suicide and Dsh In Psychosismentioning
confidence: 97%
“…It is also important to remember that, whilst it is challenging to determine how many people with psychotic illness complete an act of suicide before presenting to services, it is likely that this figure is not negligible. Suicide risk is high even in those identified as at risk for future psychosis: in one study (Hutton, Bowe, Parker, & Ford, 2011) suicide risk was investigated in a group of individuals in a treatment programme for those at ultrahigh risk (UHR) of psychosis. Of those included in the study, 59% reported suicidal ideation and 21% engaged in acts of DSH.…”
Section: Prevalence Of Suicide and Dsh In Psychosismentioning
confidence: 99%